Effect of fineness coconut shell charcoal ash on the rheological properties of bitumen - Mad. Rosni, Nurul Najihah (2016)
In recent years, a problem regarding environmental pollution due abundance waste from agricultural activities increased due to higher productivity. An approach is taken to solve this problem by recycle this agricultural waste. Coconut shell charcoal (CSC) ash is a by-product of coconut shell that is used as bitumen modifier to enhance properties of binder. This paper aims to study the effect on rheological properties of binder at different fineness of CSC. Penetration test, softening point test and viscosity test were performed to determine properties of modified bitumen. Laboratory simulation of short term aging called RTFO test was applied in this study. To conduct the test, CSC was grind for three hours then sieve to obtain different sizes. CSC at three different sizes (less than 75µm, 75-150µm, and 150-300µm) was added to replace bitumen 60/70 PEN at 10%, 15% and 20% by weight of bitumen. The result of the study shows that bitumen become more viscous and softening point of bitumen increased while rate of penetration decrease when incorporating with CSC. It is also noted that proper amount of CSC have improved resistance to temperature susceptibility. The result also indicates that modification of bitumen can relieve the effect of aging. Modified bitumen shows better result when incorporating with the finest particle (less than 75µm) of CSC compare to other sizes.